RESEARCH OF THE MODES OF FULL COMPENSATION OF REACTIVE POWER IN A THREE-PHASE POWER SUPPLY SYSTEM - V. G. Yagup (National Technical University "Kharkiv Polytechnic Institute", 2019)
Introduction The article is devoted to the issues of current balancing and reactive power compensation in a three-phase power supply system. Optimal in all these respects is the mode of full compensation of reactive power, by which we mean such a symmetrical mode, in which only active power is consumed from the source. The task of calculating the mode of full reactive power compensation is non-linear and can be solved using non-linear optimization methods based on the adopted parameters and optimization criteria. The objective of the article is to develop a visual model of the power supply system with an unbalanced load, in which current balancing and reactive power compensation is performed using a symmetrical-compensating device, which parameters are determined using search non-linear optimization tools and modern computer mathematics software packages. The purpose of the article is to research the modes of full compensation of reactive power in a three-phase power supply system with a linear asymmetric load in order to identify the ambiguity of solving the problem of synthesizing parameters of a reactive power compensator. Methodology of research consists in the development of a visual model of a power supply system that feeds unbalanced load. As a symmetrical compensating device, capacitors connected between the phases of the transmission line are used. The model is controlled by a program that launches the model and performs optimization and selection of optimization variable values. The optimization values are the capacitors of the symmetry-compensating device. The optimization criterion is a spherical metric consisting of the reactive powers of each source of electricity. Results lead depending on the choice of the initial values of the optimization variables, the optimization process enters two modes of full compensation of reactive power – main and additional. The main mode is characterized by small values of capacitors and small values of currents, and in the additional mode, these values of the system and operational parameters reach extremely large values that are unacceptable for practical use. Originality lies in the fact that in terms of optimization theory this means that there is no global optimum in the solution of the problem of full compensation, however, there are two local optimums. Both modes are stable, as evidenced by modeling on the SPS-model of the system in the time domain in the space of state variables. Practical significance of the work lies in the fact that when designing a microprocessor system that optimizes the operating mode of the power supply system, it is necessary to envisage the situation of additional mode.